Complexities in Student Placements Under COVID-19 Moral and Practical Considerations - Sarbu, Raluca; Unwin, Peter (Frontiers in Education, 2021)
Abstract : The work placements experiences of MA and BA social work students at an English University in a time of pandemic were explored by way of an online survey. Thirteen students responded and reported that the moral and practical consequences of a sudden forced move to the ‘new normal’ of online working and assessment raised serious issues about the boundary between home and work-life, and about the relationship-based nature of the career they thought they were entering. Experiences of moral and practical support from agencies were mixed, and a lack of consistency across different placement agencies led to feelings of unfairness in the student experience. Opportunities for incidental and tacit forms of learning were lacking in online working environments and students were strongly of the belief that the future of social work would entail a permanent locus shift from community work to online interaction regarding the people (service users and carers) with whom they worked. This shift was largely perceived in terms of loss, and a further diminution in relationship-based practice in English social work services, which have increasingly been dominated by a task and performance management culture before the onset of Covid-19. Key words Student placements; social work; moral complexity; work-life balance; student support; ‘new normal’; relationship-based practice; work placements